APPLICATION OF CONTEXTUAL TEACHING AND LEARNING MODEL IN DEVELOPING CRITICAL THINKING SKILLS IN FIQH THAHARAH LESSONS: A CASE STUDY AT THE ANNUR DARUNNAJAH 8 ISLAMIC BOARDING SCHOOL IN CIDOKOM, BOGOR REGENCY - Saidatul Fitri Rifadina; Armai Arief; Abdul Mukti (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model in fiqh thaharah learning and to analyse its implications for students’ critical thinking skills at Pondok Pesantren Annur Darunnajah 8 Cidokom, Bogor. Using a qualitative case study design, the research was conducted in the fiqh class of upper secondary level students. Data were collected through participatory observation, in-depth interviews with school leaders, curriculum staff, fiqh teachers, and students, as well as documentation of lesson plans and learning outcomes. Data were analysed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing, and were validated through source, technique, and time triangulation and member checking. The findings show that the CTL model has been implemented through seven core components: constructivism, inquiry, questioning, learning community, modelling, reflection, and authentic assessment, which are integrated into fiqh thaharah learning and pesantren daily practices such as wudu, maintaining cleanliness, and worship routines.